Ganoderma lucidum in broiler diets: Impact on physiological performance and productive-economic efficiency (Agroindustrial Science, 2022)
The demand for quality and safety in poultry meat can be achieved by affecting overall performance with the supply of functional nutrition, which decreases metabolic stress, lipid peroxidation, and dangerous metabolomes. The objective of this research was to evaluate the physiological performance, the productive parameters and the economic profitability when including Ganoderma powder extract. lucidum in drinking water. 480 one-day-old BB Cobb500 chickens were evaluated for 49 days under intensive rearing. A completely randomized design with 4 treatments and 4 repetitions was applied, corresponding: Without extract, 6mg/kg/pv , 12 mg/kg/pv and 18 mg/kg/pv , for 7 consecutive days of weeks 1, 2, 4th and 6th. The hematological and metabolic profile was determined on days 1, 8, 29, 42 and 50 of age. The results were evaluated by ANOVA and Tukey's test; being the greatest positive effect of Ganoderma lucidum supplementation with 18 mg/kg/bw , showing statistical significance (p < 0.05) for body weight, weight gain, feed intake and conversion, mortality, hemoglobin and transaminases. It was concluded that the inclusion of the fungus Ganoderma lucidum in the diet improves the physiological, productive and economic performance of broiler chicken.
Keywords: Ganoderma lucidum Reishi; chicken nutrition; avian physiology; cost-benefit; metabolic profile